Hubungan Antara Pengguna Media Super Smart Kids dengan Kemampuan Berhitung Anak Usia Dini - Reisa Iskilah (Journal of Islamic Education for Early Childhood, 2024)
This research aims to determine: (1) The use of super smart kids media in early childhood in the B1 group of RA Amal Bakti, Cipadung District, Bandung City; (2) The ability to count in early childhood in the B1 group of RA Amal Bakti, Cipadung District, Bandung City; (3) The relationship between the use of super smart kids media and the numeracy skills of young children in the B1 group of RA Amal Bakti, Cipadung District, Bandung City. The results of data analysis show that the use of super smart kids media obtained an average score of 66.5. This figure is in the interval 60 – 69 in the sufficient category. Meanwhile, the numeracy skills of early chilhood students obtained an average score of 77.75. This figure is in the interval 70 – 79 in the good category. The relationship between the use of super smart kids media and the numeracy skills of young children has a correlation coefficient of 0.78. This correlation coefficient figure is in the interval 0.60 – 0.80 in the good category. The significant test results show t_count=5.3>t_table=2.306. This means that Ha (alternative hypothesis) is accepted and Ho (null hypothesis) is rejected. In other words, the use of super smart kids media has a positive relationship with the numeracy skills of early chilhood students at RA Amal Bakti Bandung City. The contribution of using super smart kids media to the numeracy skills of early chilhood students is 60.84%. This means that there are still 39.16% other factors that influence early chilhood students numeracy skills.